Diagnostic ultrasound physics and equipment - Hoskins Peter; Martin Kevin; Thrush Abigail; Whittingam Tony (London GMM, 2003)
This book aimed primarily at sonographers taking the postgraduate diploma in medical ultrasound, this book provides a concise technical introduction to the subject, without going beyond the level of knowledge required. Fully illustrated throughout, with
Keywords: Diagnostic imaging